A study of micro-machined silicon vibrating gyroscope behavior using Taguchi method: article / Raja Ahmad Hafiz Saiful Bahri - Saiful Bahri, Raja Ahmad Hafiz (2013)
This thesis presents a study of Micro-machined silicon Vibrating Ring gyroscope by using ANSYS software. It concludes the process from designing the structure until the simulation. There are four control factors have been varied for four levels, which are support spring diameter, ring diameter, height of ring structure and support post diameter by using taguchi method. A research on the structure has been done to find the suitable design and parameter. The experiments were arranged involving the control factor in L16 orthogonal arrays. This method is used to find the optimum frequency from the combination of experiment. After done simulate all 16 experiment, it shows that the optimum frequency simulated in ANSYS is 11769 Hz, which is experiment 6 the combination A2B2C1D4. Based on previous work, it show that this project from experiment 6 give better resonant frequency value than previous work.